Pengaruh Pola Makan Sarapan Pagi dan Uang Jajan terhadap Memory Short Term Anak di SDI Busalangga - Sisilia L. Damian; Marselinus Laga Nur; Sarci Magdalena Toy (Yayasan Literasi Sains Indonesia, 2025)
A healthy and balanced breakfast eating pattern can provide essential nutrients needed by children's bodies for growth and development, which supports cognitive functions, including short-term memory. Many students at SDI Inpres Busalangga do not have breakfast in the morning; instead, they prefer consuming snacks at school, which leads to a lack of concentration during lessons. This study aims to determine the effect of breakfast eating patterns and pocket money on the short-term memory of students at SDI Busalangga, Rote Barat Laut District, Rote Ndao Regency. This research is a quantitative observational analytic study with a case-control design. The study involved 51 participants, consisting of fourth- and fifth-grade students at SDI Busalangga. Data analysis was conducted using simple logistic regression tests. The results showed that breakfast significantly influences short-term memory (p=0.002, OR=6.735), and pocket money also has an effect on short-term memory (p=0.014, OR=4.821). It is recommended that teachers at SDI Busalangga enhance awareness about the importance of breakfast for children and the benefits of pocket money. Additionally, efforts should be made to increase children's knowledge about healthy eating habits and the proper use of pocket money.